THE CHOICE OF ENGLISH LANGUAGE USEBASED ON CONTEXT A CASE STUDY ON STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF FKIP UNTAN - Endang Susilawati (ICoTE Proceedings)
This research was conducted for two specific objectives. The first is to figure out how appropriately the students can use English language expressions in accordance with the given context . The second is to identify what are the factors contributing the students’ ability in using appropriate English language expressions in accordance with the given context. A case study was applied to approach the solution of the problems. The data were collected from a multiple choise test and a composition writting task were administered to 36 students who were purposely selected as the participants of this research. From the findings and discussion, it is firstly concluded that there were only few students . could show their good and best category of abilility while many of them were still in poor ability Some of them were even unable to use English language Expressions appropriately in accordance with the given context. Secondly, it is concluded that there were some factors which contribute to such level of performance. The factors were dealing with the students’ ignorance of the importance of appropriateness dimension in communication in addition to fluency and accuracy; the ignorance of both various English language expressions in every interactional functions and  the existance of context within which an interactional function occurs. The rest was the factors which concern with the lackness of exposure to such learning experience, from which they could actually  practice using English language expressions in various contexts.